Comprehensive individualized approach to the treatment of patients with acute intestinal obstruction of tumor genesis - Kubrak, M. A.; Zavgorodnyi, S. M.; Danyliuk, M. B.; Chemeris, Yu. O.; Кубрак, Михайло Анатолійович; Завгородній, Сергій Миколайович; Данилюк, Михайло Богданович; Чемерис, Юлія Олександрівна (My University, 2025)
Objective. To analyze the results of using a comprehensive individualized approach to the treatment of patients with acute intestinal obstruction of tumor genesis. Materials and methods. The study included 125 patients with acute intestinal obstruction as a complication of colon cancer. Results. The use of a strategy of a comprehensive individualized approach to the treatment of acute intestinal obstruction of tumor genesis made it possible to increase the proportion of delayed surgical interventions from 65,31 to 81.08% (p = 0.0297), reduce the proportion of operations that ended in colostomy from 79.59 to 21.62% (p = 0.0081), reduce the incidence of perioperative complications from 42.86 to 17.57% (p = 0.0267) and mortality from 12.25 to 5.41% (p = 0.0491). Conclusions. The use of the developed strategy for the complex treatment of acute intestinal obstruction of tumor genesis significantly improved early perioperative outcomes in patients of this category.
Keywords: colon; cancer; complications; acute intestinal obstruction; surgical interventions; endoscopy